A porous polyethersulfone hollow fiber membrane in a gas humidification process. Issue 19 (2nd February 2015) - Bakeri, Gh.; Naeimifard, S.; Matsuura, T.; Ismail, A. F.
Abstract : Porous PES hollow fiber membrane was fabricated and characterized in terms of pore size, porosity and wettability and used in humidification process. The membrane showed high performance compared to the commercial and in-house made membranes. Abstract : A porous polyethersulfone hollow fiber membrane was fabricated via a dry–wet phase inversion process. The membrane was characterized by measuring the pore size, porosity and LEPw. Scanning electron microscopy (SEM) revealed the presence of finger-like macrovoids in the cross-section of the membrane, which contributed to the reduction of tortuosity. The fabricated membrane was further applied in gas humidification. It was found that the water flux was increased by an increase in the gas and liquid flow rates and temperature but reduced by an increase in gas pressure. The water flux of the fabricated membrane exhibited a gas humidification performance superior to a commercial humidifier, e.g. it has 380% higher water flux than the Perma Pure® 1 model PH-60T-24SS at T liquid = 40 °C.